PENGARUH KOMPOSISI BAHAN ORGANIK TERHADAP KADAR AIR DAN DAYA SERAP AIR PADA PEMBUATAN KOMPOS BLOK - Fajar Fahmi Romdoni; Nina Herlina; Iing Nasihin (Journal of Forestry And Environment, 2023)
In an effort to avoid the accumulation of polybag waste, it is necessary to look for other alternatives as a substitute for polybags that can fulfill the nutrients needed by plants and can reduce plastic waste from the use of polybags (Murdhiani Rosmaiti, 2017). One way to overcome the weaknesses of polybags is to use seedling containers made from environmentally friendly organic materials, namely Compost Blocks. The basic material for environmentally friendly Compost Blocks has the advantage of being easily decomposed and can contribute quite a lot of nutrients (END, 2018). The aim of this research is to determine the effect of the composition and type of organic material as well as the composition of organic adhesive on water content and water absorption capacity in making Compost Blocks. The research was structured based on a two-factor completely randomized design. The first factor is the composition and type of organic material (Kagot 100%, cashgot 50% + leaf litter 50%, cow dung 50% + leaf litter 50%) while the second factor is the composition of the organic adhesive (starch 5% and 10%). The composition and type of organic material as well as the composition of organic adhesive have a significant effect on the water content and water absorption capacity of making Compost Blocks.Dalam upaya menghindari penumpukan sampah polybag, maka perlu dicari alternatif lain sebagai pengganti polybag yang dapat memenuhi unsur hara yang dibutuhkan oleh tanaman dan dapat mengurangi sampah plastik dari penggunaan polybag. Salah satu cara untuk mengatasi kelemahan polybag adalah dengan penggunaan wadah semai berbahan dasar organik yang ramah lingkungan yaitu Kompos Blok. Bahan dasar Kompos Blok yang ramah lingkungan memiliki keunggulan mudah terdekomposisi dan dapat menyumbangkan unsur hara yang cukup banyak. Tujuan dari penelitian ini yaitu untuk megetahui pengaruh komposisi dan jenis bahan organik serta komposisi perekat organik terhadap kadar air dan daya serap air pada pembuatan Kompos Blok. Penelitian disusun berdasarkan rancangan acak lengkap dua faktor. Faktor pertama adalah komposisi dan jenis bahan organik (Kagot 100%, kasgot 50% + serasah daun 50%, kotoran sapi 50% + serasah daun 50%) sedangkan faktor kedua yaitu komposisi perekat organik (tepung kanji 5% dan 10%). Komposisi dan jenis bahan organik serta komposisi perekat organik berpengaruh nyata terhadap kadar air dan daya serap air pada pembuatan kompos blok